The homolog of chromatin binding protein Bx42 identified in Dictyostelium - Folk, P; Půta, F; Krpejsová, L; Blahůsková, A; Markos, A; Rabino, M; Dottin, R P (Gene, 1996)
We identified in Dictyostelium a gene snwA containing a region of similarity to SH2 domains of higher eukaryotes. snwA is homologous to a novel human gene SNW1 and to Bx42 from Drosophila melanogaster, a gene coding for a chromatin binding protein responsive to 20-OH-ecdysone. snwA has one mRNA transcript of an approximate size of 2.5 kb.
Keywords: src Homology Domains; DNA-Binding Proteins; Humans; sekvenční homologie aminokyselin; src homologní domény; DNA vazebné proteiny; Sequence Homology, Amino Acid; Protozoan Proteins; Molecular Sequence Data; molekulární sekvence - údaje; Drosophila Proteins; jaderné proteiny; chromatin; lidé; zvířata; Chromatin; Amino Acid Sequence; proteiny Drosophily; Nuclear Proteins; Dictyostelium; Animals; protozoální proteiny; sekvence aminokyselin